SLC26A4 regulates autophagy and activates the NLRP3 inflammasome to mediate pathological cardiac hypertrophy - Li-qun Tang; Ling-ling Wang; Qi-feng Tang; Wei Wang (Scientific Reports)
Abstract Solute carrier family 26 member 4 (SLC26A4) plays an essential role in the progression of pathological cardiac hypertrophy. This study aimed to examine the involvement of SLC26A4 in cardiac hypertrophy by regulation of autophagy and activation of the NOD-like receptor thermal protein domain associated protein 3 (NLRP3) inflammasome. Cardiomyocytes were treated with 200 µmol/L phenylephrine (PE) to induce cardiac hypertrophy, followed by treatment with 10 mmol/L INF39, an NLRP3 inhibitor. Furthermore, the pLL3.7 lentiviral vector was used to construct a sh-SLC26A4 interference plasmid and a PLL3.7-cardiomyocytesv-SLC26A4 overexpression plasmid to intervene in PE-induced cardiac hypertrophy. Quantitative reverse transcription polymerase chain reaction and Western blotting were performed to measure the expression of ANP, BNP, β-MHC, SLC26A4, NLRP3, apoptosis associated speck-like protein containing a C-terminal caspase recruitment domain (ASC), and caspase-1. Immunofluorescence was used to detect the level of α-smooth muscle actin (α-SMA) to indicate the cardiomyocyte area. The expression levels of the autophagy proteins LC3, beclin-1, and p62 were determined by Western blotting. Finally, an SD rats model of cardiac hypertrophy was established using transverse aortic constriction (TAC) surgery. SLC26A4, NLRP3, IL-1β, ACS and caspase-1 were further examined at gene and protein levels. SLC26A4 expression was associated with cardiac hypertrophy in cell experiments. SLC26A4 promoted autophagy and activation of the NLRP3 inflammasome pathway, regulating the gene and protein expression of LC3, beclin-1, p62, ACS, NLRP3, and caspase-1. Similar results were observed in the TAC rat model, in which SLC26A4 expression was associated with cardiomyocyte enlargement and cardiac interstitial and perivascular fibrosis. SLC26A4 was involved in cardiac hypertrophy by promoting autophagy and activating the NLRP3 inflammasome pathway. Targeting the expression of SLC26A4 may provide a new treatment option for cardiac hypertrophy.